Assessment of the impact on the care of patients with detaching wounds during the COVID-19 pandemic in a specialized service - Gustavo Moreira Clivatti; Dimas André Milcheski; Danielle Nunes Briza; Renan Diego Américo Ribeiro; Laielly Abbas; Gustavo Gomes Ribeiro Monteiro; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica)
Introduction: The COVID-19 pandemic was responsible for increasing social isolation rates, resulting in a reduction in traffic accidents. Trauma, in general, is among the most important public health problems worldwide. This study aims to evaluate the impact of social isolation in the city of São Paulo during the COVID-19 pandemic on the care of patients with detaching wounds. Methods: Observational, retrospective and descriptive study. All medical records of patients treated at the Emergency Room of the Hospital das Clínicas of the Faculty of Medicine of the University of São Paulo (HCFMUSP), by the Complex Wounds Group of the Plastic Surgery Service, admitted for detaching wounds and undergoing surgical procedures, were reviewed, from April to June of the years 2019 and 2020. Results: Twenty patients with detaching injuries on the lower limbs were included. In 2019, 14 patients were seen, with a mean age of 47 years, 7 of which were victims of traffic accidents, 5 of being run over, 1 of crushing and 1 of falling from standing height. In 2020, 6 patients were treated with detaching wounds during the pandemic, with a mean age of 36.16 years, 5 of which were victims of motorcycle accidents and 1 of being run over. No patient had COVID-19. Conclusion: During social isolation, there was a numerical reduction in care for detaching trauma during the quarantine period.